E-Contract Withdrawal Rights in E-Commerce: A Comparative Analysis of the Egyptian Consumer Protection Law and Islamic Jurisprudential Perspectives - Azam, Muhammad; Al-Farjani, Saleh Hashem; Mashdurohatun, Anis; Elsonbaty, Atta; Salman, Mohammed Abdullah (Universitas Islam Sultan Agung, 2025)
This research examines the right of withdrawal in e-contracts within the realm of e-commerce, specifically under the Egyptian Consumer Protection Law No. 181 of 2018, through the lens of Islamic jurisprudence. The study focuses on the practical application of the right of withdrawal in e-commerce, particularly concerning the consumer's ability to cancel a contract post-purchase without the opportunity for physical inspection of the goods. The objective is to elucidate the conceptual framework, statutory basis, and practical implications of the right of withdrawal within both the Islamic and Egyptian legal systems, as well as to evaluate its effectiveness in safeguarding consumer rights. The research adopts a qualitative methodology with a comparative analytical approach, encompassing an examination of the principles of Islamic jurisprudence, the relevant provisions of Egyptian legislation, a thorough analysis of statutory texts, and the perspectives of legal scholars. The findings indicate that both Islamic jurisprudence and Egyptian legislation acknowledge the consumer's right to withdraw under specific conditions. Nonetheless, practical limitations persist, particularly in the digital marketplace, where product characteristics and the logistics of returning goods pose challenges to the enforcement of consumer rights. This study contributes by presenting a comprehensive comparison between traditional Islamic options (khiyār al-ru'yah, khiyār al-'ayb, khiyār al-Shart) and contemporary legislative mechanisms, thereby highlighting their mutual aim of protecting the weaker party in transactions. It is anticipated that the Egyptian government will amend Article 40 of the Consumer Protection Law to ensure a fair allocation of costs associated with the return of goods between consumers and sellers. Furthermore, the significance of consumers' understanding of their rights and responsibilities regarding the recall of goods within the electronic contract framework must be emphasised.